A qualitative study of the attitudes of South African spaza shop owners to coopetitive relationships - Charles Hare; David Walwyn (South African Journal of Business Management, 2019)
Background: Coopetition is a powerful means by which microenterprises can compete against large firms in low margin sectors, such as the small retail outlets in South African townships, known locally as spaza shops. Although coopetition is widely used by foreign nationals who own and manage such shops, and who are reported to be more successful, South African owners have failed to establish such relationships.Objectives: The objective of this study was to explore the reasons why South African owners do not form such relationshipsMethod: The study used a qualitative, exploratory approach.Results: An absence of trust and a general lack of awareness of the potential benefits of coopetition are the major barriers. Moreover, the volatile environment within which these spaza shops operate, characterised by extensive unemployment and high crime rates, and makes the establishment of coopetitive relationships more difficult.Conclusion: Any intervention designed to improve the survival rate of spaza shops should include measures to address Issues of trust and the benefits of coopetitive relationships.
Keywords: 650